1998
DOI: 10.1002/(sici)1097-4628(19981226)70:13<2619::aid-app7>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on flocculation characteristics of polysaccharide-based graft copolymers in coal fines suspension

Abstract: ABSTRACT:The article deals with the synthesis of two polysaccharide-based graft copolymers of acrylamide, namely, starch-g-polyacrylamide (St-g-PAM) and amylopecting-polyacrylamide (Ap-g-PAM). Intrinsic viscosity of the graft copolymers was determined. A flocculation jar test was carried out with Ϫ200# ASTM particles for two coking and two noncoking coal samples from Indian coalfields. It is observed that both the grafted products are very effective flocculants in bringing down the turbidity of supernatant liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…By grafting of synthetic polymers onto natural polysaccharide backbone, it is possible to combine the best properties of both. It has been observed that by grafting synthetic polymers onto natural polysaccharide backbone, it is possible to develop efficient flocculants with improved flocculation properties (Karmakar, Rath, Sastry, & Singh, 1998;Sen, Kumar, Ghosh, & Pal, 2009;Singh et al, 2000;Singh, Nayak, Biswal, Tripathy, & Banik, 2003;Tripathy & Singh, 2001). These graft copolymers are biodegradable as well as non-toxic in nature (Vijan, Kaity, Biswas, Issac, & Ghosh, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…By grafting of synthetic polymers onto natural polysaccharide backbone, it is possible to combine the best properties of both. It has been observed that by grafting synthetic polymers onto natural polysaccharide backbone, it is possible to develop efficient flocculants with improved flocculation properties (Karmakar, Rath, Sastry, & Singh, 1998;Sen, Kumar, Ghosh, & Pal, 2009;Singh et al, 2000;Singh, Nayak, Biswal, Tripathy, & Banik, 2003;Tripathy & Singh, 2001). These graft copolymers are biodegradable as well as non-toxic in nature (Vijan, Kaity, Biswas, Issac, & Ghosh, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The graft copolymers have also been found to be reasonably shear stable5 because of the attachment of flexible synthetic polymers onto their rigid polysaccharide backbones. The study of flocculation characteristics of the graft copolymers of polyacrylamide and various polysaccharides such as guargum, starch, and xanthagum6–8 has proven that each of the graft copolymers is a better flocculating agent than polyacrylamide. Based on the previously mentioned studies, a model was proposed by Singh2 that the better efficiency of graft copolymers compared to the linear polyacrylamide was probably caused by better approachability of the branched chains to the colloidal particles.…”
Section: Introductionmentioning
confidence: 99%
“…Anionic, cationic and nonionic synthetic as well as natural polymers are widely used. Among the natural polymers polysaccharides have been used extensively but their performance is not good [3]. On the other hand polyacrylamide based synthetic polymers are very efficient flocculating agents but they are shear degradable.…”
Section: Introductionmentioning
confidence: 99%